Winter prey - Sandford, John, 1944 February 23- (Sandford, John, 1944 February 23- Prey novel., 1993)
In a rural area of northern Wisconsin, a family of three is savagely wiped out by the Iceman, who then torches their house. In pursuit of a damaging photograph, this fiend puts no value on human life. Enter Davenport, the laconic, slightly cynical ex-cop from Minneapolis, who uncovers several disturbing truths before determining the Iceman's identity.